2018
DOI: 10.1159/000487855
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease, Melanoma, and Keratinocyte Carcinoma: A Population-Based Study

Abstract: Background: The association between Parkinson’s disease (PD) and melanoma is well recognized, but its relationship with non-melanoma skin cancers has not been studied in depth. Objective: To assess the relationship between PD, and risk of melanoma and keratinocyte carcinoma: squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). Methods: This historical cohort study used the data of 1.2 million adult members of a large health organization between 2000 and 2015. Individuals who were diagnosed with PD any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…A positive family history of melanoma has also been shown to increase the risk of PD [29]. Not all studies support the association between PD and melanoma as noted in the meta-analyses; in a large study from Israel including more than 1.2 million members of a health organization followed from 2000 to 2015, there was no increased risk of melanoma after a diagnosis of PD, but the study suggested a higher risk of basal cell carcinoma [30]. A higher risk of non-melanoma skin cancers in PD versus controls [28] and in LRRK2-PD versus idiopathic PD [31] has also been suggested.…”
Section: Melanomamentioning
confidence: 96%
“…A positive family history of melanoma has also been shown to increase the risk of PD [29]. Not all studies support the association between PD and melanoma as noted in the meta-analyses; in a large study from Israel including more than 1.2 million members of a health organization followed from 2000 to 2015, there was no increased risk of melanoma after a diagnosis of PD, but the study suggested a higher risk of basal cell carcinoma [30]. A higher risk of non-melanoma skin cancers in PD versus controls [28] and in LRRK2-PD versus idiopathic PD [31] has also been suggested.…”
Section: Melanomamentioning
confidence: 96%
“…Additionally, we also looked for any association between skin cancer and Parkinson’s disease or IBD, which have been suggested as possible comorbidities associated with skin cancer in several previous studies. The association between melanoma and Parkinson’s disease has been demonstrated in several previous studies [ 3 , 33 ]. In addition to L-dopa treatment in patients with Parkinson’s disease, several common genes found in both patients with Parkinson’s disease and melanoma have been suggested to be involved in the association between these two diseases [ 3 , 33 ].…”
Section: Discussionmentioning
confidence: 64%
“…The association between melanoma and Parkinson’s disease has been demonstrated in several previous studies [ 3 , 33 ]. In addition to L-dopa treatment in patients with Parkinson’s disease, several common genes found in both patients with Parkinson’s disease and melanoma have been suggested to be involved in the association between these two diseases [ 3 , 33 ]. Recently, in addition to melanoma, an increased risk of developing basal cell carcinoma has also been reported in patients with Parkinson’s disease [ 3 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations